Kyrgyz Republic : Request for Purchase Under the Rapid Financing Instrument and Disbursement under the Rapid Credit Facility-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2020)
This paper focuses on the Kyrgyz Republic's Request for Purchase Under the Rapid Financing Instrument and Disbursement Under the Rapid Credit Facility. The coronavirus disease 2019 pandemic has hit the Kyrgyz economy very hard and increased an already urgent balance of payments need. All sectors are being severely affected while measures are being taken to stop the spread of the virus. The IMF emergency support addresses the urgent balance of payments need, shores up confidence, and catalyzes donor support. In order to ensure that the financing provided is efficiently spent on addressing the crisis, the authorities have committed to strengthen procurement rules. The health care contingency plan and the initial package of economic measures already adopted by the authorities to provide health and economic relief are welcome, as is the second, larger, package of measures under preparation. In their attached letter of intent, the authorities remain committed to temporarily loosening macroeconomic and financial policies to finance health and economic relief and support a recovery. They have also made additional commitments to strengthen procurement rules, including steps to enhance transparency, to help ensure that financing received is efficiently spent on addressing the crisis.